Qanun of Islamic Financial Institutions Implementation and Cooperatives Responses: Experience from Aceh - Khairil Umuri; Teuku Muhammad Syahrizal; Hendra Halim; Junia Farma (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
Implementing Qanun No. 10 of 2018 concerning Islamic Financial Institutions requires that every financial institution in Aceh must operate according to sharia principles. Cooperatives, a financial institution in Aceh, are also required to convert into sharia cooperatives. In the journey of becoming a sharia cooperative, several obstacles are faced. So, this study wants to analyze how the readiness of cooperatives in Aceh to convert into sharia cooperatives. The research uses a qualitative approach with descriptive analysis in the form of a field (filed research). The results found, firstly, several obstacles faced by cooperatives in the conversion process, such as a lack of understanding of cooperative management towards LKS qanuns, lack of support from local governments, burdensome changes to AD/ART, and the lack of cooperative DPS. Conversion process activities can be carried out by changing AD/ART according to sharia legality, changing managerial, IT and contract systems according to sharia, and providing understanding to cooperative management and members about sharia cooperatives. In addition, training and socialization regarding sharia cooperatives are also needed, as well as encouraging religious activities. So to support the conversion process, support from all related parties is needed, such as the Cooperatives and SMEs service, the Aceh Aceh Sharia Council (DSA), and the cooperative.